Phosphate adsorption characteristics of crushed red bricks - Joanna, Uding Thayun. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Phosphates present in domestic wastewater causes eutrophication. The wastewater treatment system in Kuching would never be able to overcome this problem. Ecological sanitation (ecosan) is an environmentally more efficient way to treat domestic wastewater. The constructed wetland in Ecosan functions in trapping phosphates, preventing them from flowing freely into storm water drains. The substrate in the constructed wetland may play the greatest role in trapping the phosphates. In this study, the adsorption capability of crushed red bricks was examined using the sequential system and the semi-batch system. In the sequential system, six different flow rates were examined and the size of adsorbents used was in the range of 4-10 mm. At the flow rate of 11.83 mU min, 1.6 mg! kg of phosphates were removed, at 5.75 mU min, 0.9 mg! kg of phosphates were removed, at 2.58 mU min, 1.3 mg/ kg of phosphates were removed, at 1.78 mU min, 1.3 mg! kg of phosphates were removed, at 1.50 mU min, 1.6 mg! kg of phosphates were removed and at 1.06 mU min, as much as 1.3 mg! kg of phosphates were removed. With the semibatch system and using adsorbents with the size in the range of 4-10 mm, 1.8 mg! kg of phosphates were removed after 24 hours and after 48 hours, 2.0 mg! kg of phosphates were also removed. After crushing the bricks to a smaller size, which is in the range of 2-4 mm, 2.5 mg! kg of phosphates were removed after 24 hours and 3.5 mg! kg of phosphates were removed after 48 hours. This shows that the semi-batch system was able to remove phosphates more efficiently due to more contact of the phosphates with the adsorbents through this method. From the sequential system, although adsorption occurs straight away, only a limited amount of phosphates was removed. Smaller size of the adsorbent increases su rface area and enables more phosphates to be adsorbed.